Fascistization and the Upper Education: the future of the university in check - Duarte, Janaína; Lima, Kátia (Argumentum, 2022)
The text analyzes the offensive of the capital to the upper public education, particularly, the intense reconfiguration of the federal universities conducted by the governments Michel Temer (2016-2018) and Jair Bolsonaro (2019-in progress). Based on the dialog of Florestan Fernandes work, it examines the changes in the upper education policy in the period indicated above, evidencing that there is an attack to the financial autonomy showing that an attack is underway on the financial and management autonomy of federal universities, linked to their political-pedagogical reconfiguration, especially by the underfunding of public upper education, through the intervention of the federal government in choosing the deans of federal educational institutions and through the Future-se program. Finally, the text presents some indications for collective struggles in defense of the public university, especially in a context of pandemic and fascistization of power structures.